Rancang Bangun Mesin Pemarut Batang Putak - Vinsen Yuminto Bifel; Defmit B.N. Riwu; Jack C.A. Pah (Jurusan Teknik Mesin, Fakultas Sains dan Teknik, Universitas Nusa Cendana, 2021)
Putak is the name of a local feed on the island of Timor, East Nusa Tenggara which is obtained from the trunk of the gewang tree (Coypha gebanga). Most of the putak processing by the people of Timor Island is very low and also limited so that putak productivity is very low because people still do it traditionally and only use it as food. Therefore, this study aims to design a putak grater for animal feed. The VDI 2221 method is a design method that uses a systematic approach to design for engineering systems and engineering products. The effective capacity of the tool is obtained by grating / repeating 3 times, then the average effective capacity of the tool is calculated. In testing the putak sticks used to produce a grated mass volume of 3,5 kg, and a tool capacity of 70 kg/hour. The results showed that the effective capacity of the putak grating machine was 70 kg/hour.